Plant Community Effects and Genetic Diversity of Post-fire Princess Tree (Paulownia tomentosa) Invasions. (7th July 2017) - Lovenshimer, Joseph B.; Madritch, Michael D.
Abstract : Many naturalized populations of the invasive tree princess tree exist in North America, yet little research has quantified its effect on native plant communities. A series of recent wildfires in the Linville Gorge Wilderness Area (LGWA) promoted multiple large-scale princess tree invasions in this ecologically important area. To measure community shifts caused by these princess tree invasions across burn areas, we sampled vegetation in paired invaded and noninvaded plots in mature and immature invasions within two burn areas of the LGWA. Plant community composition shifted in response to princess tree invasion across all invasion stages and burn areas. Species richness and Shannon diversity values decreased in invaded plots. Overall community structure also differed in invaded plots within immature invasions (P=0.004). The distribution of princess tree age classes in both burn areas indicates that fire promotes invasion but is not necessary for subsequent recruitment. Additionally, preliminary genetic analyses among distinct princess tree populations revealed very low genetic diversity, suggesting that a single introduction may have occurred in the LGWA. This information regarding community shift and strong post-fire recruitment by princess tree may inform management decisions by prioritizing princess tree control immediately after wildfires and immediately before and after prescribed burns.